Efficacy and Safety of Cannabidiol for Anxiety: A Bibliometric Analysis and Systematic Review - Putu Ayu Putri Fajaryani; I Made Agus Gelgel Wirasuta; Pande Made Nova Armita Sari; Dyah Kanya Wati; Putu Indah Budi Apsari; Made Ary Sarasmita (Pusat Pengembangan Teknologi Informasi dan Jurnal Universitas Muhammadiyah Palu, 2025)
Introduction: A non-psychoactive substance present in the cannabis plant, cannabidiol (CBD), seems to have potential as an anxiolytic agent. This study systematically reviews the efficacy, safety, dosage, mechanisms, and adverse effects of CBD in treating anxiety. Methods: The PRISMA guideline was used to conduct the review. Results: A total of 64 articles were included in the study. It showed that CBD works at the endocannabinoid receptors CB1 and 5-HT1A, which regulate mood and reduce anxiety. In animal models, a range dosage of 5 – 10 mg/kg showed a significant anxiolytic effect in behavioral tests, while in humans, 300 mg/day was proven to be effective in treating various types of anxiety disorders. However, individual responses to CBD showed varying results, and demographic characteristics affect the efficacy of animal and human studies. CBD was also considered safer to be used in the short term compared to diazepam, although the long-term effect remains lacking evidence Conclusion: This study concludes that CBD has potential as an alternative choice for anxiety. Further research is needed in larger populations with rigorous study design and longer study durations to evaluate its effectiveness and ensure its safety. Recommendations for Future Research: It is hoped that future research can examine the effects of fly resistance and killing on non-target organisms and control environmental conditions.